Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Handphone VIVO di Transcom Gunungsitoli - Erna Kristiani Zendrato; Otanius Laia; Meiman Hidayat Waruwu; Yupiter Mendrofa (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
This research aims to determine the influence of product quality and promotion on purchasing decisions for Vivo cellphones at Transcom Gunungsitoli. This research uses 3 variables, namely product quality (X1), promotion (X2) and purchasing decisions (Y) with the data source, namely primary data with collection techniques. data through a questionnaire with a sample size of 30 respondents. The type of research used in this research is Quantitative Research, from the results of the research it is concluded that the results of the calculation of the validity test of the questionnaire items for the Product Quality variable (X1) and Promotion Variable (X2) were found to meet the validation requirements because, with a sample size of 30 and sig .2-tailed 0.05, the r table value is 0.361 and is based on the spss processing table above. The calculated r value for each questionnaire data is greater than 0.362, so it can be said that the questionnaire data is valid and the results of calculating the validity of the questionnaire items for the purchasing decision variable (Y) found that it meets the validation requirements because based on the results of the r-calculated research all the question items have a value. greater than r-table, 0.361 (r-count>r-table). So it is declared valid.